Pengaruh Kegiatan Menggunting Terhadap Kemampuan Motorik Halus Anak Kelompok B di TK Negeri Pembina KH Dewantoro Kota Selatan Kota Gorontalo - Desvianti Damaling; Maryam Rahim; Pupung Puspa Ardini (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study aims to investigate the effect of cutting activities on the fine motor skills of Group B children at TK State Pembina KH Dewantoro Kindergarten, South City, Gorontalo City. An experimental method with a one-group pretest-posttest design was used. The study was conducted over two months, involving 21 children as the sample. Data collection was carried out using a performance test. A pre-test was performed to measure fine motor skills before the intervention, followed by the implementation of a cutting activity with paper for eight sessions. After the intervention, a post-test was conducted to assess changes in the children's fine motor skills. The results showed that the average score of fine motor skills before the intervention was 56.75, which increased to 88.76 after the intervention. The t-test revealed a t-statistic value of -24.720 and a p-value of 0.000, indicating that the p-value is less than the established significance level (0.05). Thus, the null hypothesis is rejected, and the alternative hypothesis is accepted, indicating that the cutting activity had a significant effect on improving the children's fine motor skills. These findings confirm that the cutting activities applied were effective in improving the fine motor skills of children at TK State Pembina KH Dewantoro Kindergarten.